2021
DOI: 10.1111/cge.13951
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic analysis of 101 patients with developmental delay or intellectual disability using whole‐exome sequencing

Abstract: Whole‐exome sequencing (WES) enables identification of pathogenic variants, including copy number variants (CNVs). In this study, we performed WES in 101 Japanese patients with unexplained developmental delay (DD) or intellectual disability (ID) (63 males and 38 females), 98 of them with trio‐WES. Pathogenic variants were identified in 54 cases (53.5%), including four cases with pathogenic CNVs. In one case, a pathogenic variant was identified by reanalysis of exome data; and in two cases, two molecular diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 55 publications
8
17
1
Order By: Relevance
“…In this study, WES was performed for 17 probands with DD/ID with an overall diagnostic yield of 58.8% (10/17), which is consistent with a recent study that WES identified pathogenic variants in 53.5% (54/101) of patients with DD/ID ( Hiraide et al, 2021 ). A total of eight de novo variants were detected, including five SNVs/Indels and three CNVs, corroborating the burden of de novo variants in DD/ID ( Brunet et al, 2021 ).…”
Section: Discussionsupporting
confidence: 87%
“…In this study, WES was performed for 17 probands with DD/ID with an overall diagnostic yield of 58.8% (10/17), which is consistent with a recent study that WES identified pathogenic variants in 53.5% (54/101) of patients with DD/ID ( Hiraide et al, 2021 ). A total of eight de novo variants were detected, including five SNVs/Indels and three CNVs, corroborating the burden of de novo variants in DD/ID ( Brunet et al, 2021 ).…”
Section: Discussionsupporting
confidence: 87%
“…In 2021, a large‐scale exome sequencing study that aimed to identify genes implicated in neurodevelopmental disorders (Wang et al, 2020) reported clinical information for 13 additional cases of CRD. In addition, a few case reports have described the clinical features of subjects with CRD (Bastaki et al, 2017; Chen et al, 2019; Hiraide et al, 2021; Hori et al, 2017). Based on these publications, CRD is currently described as an autosomal dominant neurodevelopmental disorder associated with the ID, feeding difficulties/failure to thrive (FTT), microcephaly, and behavioral abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear how much of the missing heritability of SLD could be attributed to rare or de novo variants of moderate or high effect, even though this issue has been extensively studied with respect to ID, ASD and developmental delay [142][143][144]. With the emergence of NGS technology, the identification of rare variants could help fill in some of the missing pieces of the puzzle.…”
Section: Next-generation Sequencingmentioning
confidence: 99%